Facial pain due to elongated styloid process - Indu Bhusan Kar; Niranjan Mishra; Subhrajit Raut; Akhilesh Kumar Singh (Contemporary Clinical Dentistry, 2013)
Pain is the most frequent cause of suffering and disability. The etiology of orofacial pain is still elusive. However, the etiology has to be ascertained for definitive treatment. Only after a systematic and careful evaluation can a treating surgeon be aware of the underlying cause. Though dental causes predominate in the diagnosis of orofacial pain, the rare cause of facial pain have to be excluded, which would prevent unnecessary and fruitless dental treatment. The present case is an example of a rare condition that may be overlooked during examination. This paper will describe a case of vague unilateral orofacial pain, the diagnosis of which zeroed down to an elongated styloid process.